Efecto del espaciamiento en plantación sobre dos propiedades físicas de madera de teca a lo largo del fuste - Moya Roque, Róger; Arce Ledezma, Víctor (Instituto de Ecología, A.C., 2016)
To estimate of the specific gravity and wood shrinkage of teakwood (Tectona grandis Linn F.) 10-year-old trees from plantations with two planting densities (830 trees ha-1 or 6 m x 2 m spacing and 1 100 trees ha-1 or 3 m x 3 m spacing) were studied in the dry zone of Costa Rica. Specimens of all diametric categories found in the plantations were included  in the selection of sample trees. For each one of the plantation densities, a total of nine trees were selected randomly. From each tree, cross-section samples were taken every 2,5 m along the stem length, starting at the base of the tree and up to 15 m. Specific gravity and wood shrinkage (tangential, radial, and volumetric) presented a linear relationship (2nd grade) with increasing cambium age. Statistical analysis showed that specific gravity values were greater on the 3 m x 3 m spacing, while wood shrinkage values were greater for the 6 m x 2 m spacing. The results obtained show that for 10-year-old teak trees, specific gravity is not a good indicator for predicting wood shrinkage.